Pernicious ignorance and the marginalisation of third space professionals: reflections on lived experience - Dustin Hosseini (Journal of Learning Development in Higher Education)
This article is part reflection and part case study based upon my work as a third space worker (Whitchurch, 2023a) since at least 2010. I will surface a recurring challenge encompassing the recognition and visibility of third space professionals in higher education as educators who experience silencing stemming from pernicious ignorance. Accordingly, I use Dotson’s notion of pernicious ignorance (2011, p.238) to analyse a reflective vignette to illustrate a challenge that undermines third space practitioners. The aim is to equip readers with theory that they can use to counter negative workplace behaviours, whether observed, experienced, or both, while strengthening their positions as third space professionals.